Intrinsic high refractive index polymers. Issue 1 (5th November 2014) - Macdonald, Emily K.; Shaver, Michael P.
<x xml:space="preserve">Abstract</x> Intrinsic High Refractive Index Polymers (HRIPs) are of high importance to modern technologies. Halogen, sulfur, phosphorus, silicon and organometallic rich HRIPs are highlighted. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>